The influence of managerial ability and business strategy on tax avoidance - Nabila, Amanda Zealza; Masripah, Masripah (WIM Solusi Prima, 2025)
This research aims to examine the influence of managerial ability and business strategy on tax avoidance using control variables, namely leverage and profitability. The proxy used for tax avoidance is Abnormal Book Tax Difference (ABTD). Quantitative research and using manufacturing companies listed on the IDX for the 2019-2022 period as research objects. The sampling technique used purposive sampling with a total sample of 580 samples obtained from 145 manufacturing companies. Hypothesis tests have been carried out so that it can be concluded that 1) managerial ability has a positive effect on tax avoidance; 2) Business strategy has no influence on tax avoidance.